Preparation and Properties of ZnO:Ce/Poly(methyl methacrylate) Nanocomposites via in situ Copolymerization - Yang, Benhong; Li, Meng; Wu, Yun; Zhang, Yunran; Deng, Chonghai (Asian Journal of Chemistry, 2014)
Novel inorganic/polymer nanocomposites were prepared by using in situ copolymerization of the modified inorganic nano-ZnO:Ce and methyl methacrylate. X-ray diffraction and SEM were employed to characterize the structure and morphology. Tensile test and TGA show that the incorporation of ZnO:Ce nanoparticles into poly(methyl methacrylate) matrix can significantly improve the mechanical and thermal properties of the composite.